2022
DOI: 10.1080/21645515.2021.2016009
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacists’ willingness and barriers to provide vaccination during COVID-19 pandemic in Jordan

Abstract: Providing vaccination in community pharmacies could increase the vaccination coverage rate as well as help reducing the workload of the healthcare system. The current study was conducted to evaluate community pharmacists’ willingness and barriers to provide vaccination in community pharmacy setting. A validated questionnaire which included eight items to evaluate willingness and eleven items to evaluate the barriers to provide vaccines was distributed online. Binary logistic regression was conducted to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 21 publications
(35 reference statements)
3
25
1
Order By: Relevance
“…The majority of the study population showing readiness to initiate pharmacy-based vaccination services in the UAE is consistent with similar studies conducted in the region. 11,12 In the cross-sectional survey that assessed Jordanian community pharmacists' readiness and willingness to deliver vaccination services, 64.5% of qualified pharmacists were willing to vaccinate patients and 65.0% of unqualified participants were willing to receive the required training and qualifications to be able to vaccinate. 11 Another cross-sectional online survey of Jordanian community pharmacists found that that 86.6% of respondents had a high level of willingness to administer vaccines in the community pharmacy setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the study population showing readiness to initiate pharmacy-based vaccination services in the UAE is consistent with similar studies conducted in the region. 11,12 In the cross-sectional survey that assessed Jordanian community pharmacists' readiness and willingness to deliver vaccination services, 64.5% of qualified pharmacists were willing to vaccinate patients and 65.0% of unqualified participants were willing to receive the required training and qualifications to be able to vaccinate. 11 Another cross-sectional online survey of Jordanian community pharmacists found that that 86.6% of respondents had a high level of willingness to administer vaccines in the community pharmacy setting.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although vaccine administration is not yet a service provided by the majority of community pharmacists in the United Arab Emirates (UAE), studies from Jordan and Saudi Arabia suggest that community pharmacists in the region have shown great willingness to deliver pharmacy-based vaccination services. 9,11,12 Considering the international and regional shifts towards pharmacy-based vaccinations, the objectives of this study were: i) to assess the readiness of community pharmacies in the UAE to start pharmacy-based vaccination services; ii) analyse if community pharmacists are willing to undertake relevant training; and iii) explore factors influencing pharmacists' initiation of community-based vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread intention to offer vaccination in community pharmacies, the current study discovered various barriers to vaccination. Implementation of training courses and educational initiatives should be considered to remove changeable barriers and improve accessibility to pharmacist-delivered immunization services [35].…”
Section: Yang Et Al (2015) -Chinamentioning
confidence: 99%
“…Be it global, national, state, regional, and institutional, the pharmacists have a responsibility to promote public health [66]. In this article review, several interventions have highlighted the emerging roles of community pharmacists on public health especially on smoking cessation [7][8][9][10][11][12][13][14], weight management [15][16][17][18]68], COVID-19 [58][59][60][61], chronic disease management [19][20][21][22][23][24][25]62], drug misuse prevention and management [26][27][28][29][30][31], and immunization and vaccination [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46].…”
Section: Noori Istehkam Et Al (2020) -Malaysiamentioning
confidence: 99%
See 1 more Smart Citation